Makna Mumarah Menurut Aswadi Syuhadak dalam Buku Mujadalah dalam Dakwah: Debat, Diskusi, Musyawarah Perspektif Al-Qur’an - Wahyuddin Wahyuddin; Moh. Saifulloh; Samsuriyanto Samsuriyanto (CV. ULIL ALBAB CORP, 2023)
Tafsir is the effort of scholars to understand the meaning of the Qur’an. Understanding the Qur’an must go through the guidance of straight scholars, not the guidance of lust. The type of method in this research is descriptive analysis. This study uses qualitative data that is relevant to the theme being discussed and the data used is based on Aswadi Syuhadak's book entitled Mujadalah dalam Dakwah; Debat, Diskusi, Musyawarah Perspektif al-Qur’an published by Dakwah Digital Press Surabaya in 2007. Aswadi Syuhadak in providing the etymological definition of mumarah by quoting from scholars such as Ibn Faris and Aliy Abd al-Wahid Wafiy. Lexically, citing the opinion of Ibn Manzur and Murtadla az-Zabidiy. As for the terminological meaning, Aswadi Syuhadak cites the opinion of al-Ghazaliy. Aswadi Syuhadak interprets the meaning of mumarah to be understood based on QS. Al-Kahf [18]: 22 concerning the interpretations of al-Alusiy, al-Ragib, al-Qurthubiy, and al-Maraghiy as well as the hadith narrated from Anas bin Malik in the Hadith Book of Sunan al-Tirmidhiy. According to Aswadi Syuhadak, the essence of the meaning of mumarah is harassing other people. This research is important to read so that we can understand that the Qur'an and Hadith motivate us to respect others.